Design, synthesis and evaluation of new ligustrazine derivatives as potential plasma-stable neuroprotective agents12. Issue 3 (22nd February 2017) - Zhang, Chenze; Yan, Wenqiang; Zhao, Rui; Xu, Bing; Fang, Xiong; Yan, Mengmeng; Zhang, Yuzhong; Wang, Penglong; Lei, Haimin
Abstract : To investigate plasma-stable neuroprotective agents, a series of new ligustrazine derivatives were synthesized by conjoining ligustrazine and phenols with ester, ether and amide bonds. Abstract : A series of ligustrazine–phenolic acid esters which exhibited promising neuroprotective activities have previously been reported. Nevertheless, we found that these ester compounds (likeT-VA ) were not stable in plasma by further in vivo studies. To investigate plasma-stable neuroprotective agents, a series of new ligustrazine derivatives were synthesized by conjoining ligustrazine and phenols with ester, ether and amide bonds. Most of the compounds exhibited higher protective effects against CoCl2 -induced neurotoxicity in differentiated PC12 cells than ligustrazine. Structure–activity relationships were also briefly discussed. We found that compound2c (2-((2-methoxy-4-(((3, 5, 6-trimethylpyrazin-2-yl)methoxy) methyl)phenoxy)methyl)-3, 5, 6-trimethylpyrazine) displayed the highest protective effect on the PC12 cells damaged by CoCl2 (EC50 = 1.07 μM). Preliminary stability investigation in rat plasma was verified in vitro and better plasma stability was observed with2c in comparison toT-VA .